Immunohistochemistry for Mismatch Repair (MMR) Proteins in Endometrial Cancer (Mugda Medical College Journal, 2026)
A cross-sectional study was conducted in the Department of Gynaecological Oncology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between January and December of 2023, to evaluate the immunohistochemistry findings for mismatch repair (MMR) proteins in endometrial cancer. A total of 54 endometrial carcinoma patients diagnosed by fractional curettage or diagnostic curettage admitted into the BSMMU Hospital were enrolled in this study. Patient’s history (including age, BMI, family history, parity, menstrual pattern, comorbidities, clinical complaints, investigations and operation notes) was recorded in data collection sheet. After surgery, blocks were made from pathological specimens for histopathological examination. After regular histopathological examination, assessment of the MMR status of each patient’s tumour was determined by immunohistochemistry by using monoclonal mouse antibodies against MMR proteins (MLH1, MSH2, MSH6, and PMS2) following the Dako EnVision method according to manufacturer protocol (in the Department of Pathology of the same institution). Immunohistochemistry findings revealed that two-thirds (63%) of the patients had intact expression of all MMR protein (MMRp), while 37% had a loss of expression of any of the proteins, which is known as mismatch repair deficiency (dMMR) state. Among them, the most common MMR defect identified was combined loss of MLH1/PMS2 in 9(16.67%) cases, followed by isolated PMS2 loss or isolated MSH2 loss in 6(11.11%) cases, combined MSH2/MSH6 loss in 4(7.4%) cases, while loss of all four proteins was observed in only 1(1.85%) case (Table-III). Deeper myometrial invasion (e”50%) was more evident in MMRp tumours compared to dMMR tumours (p